FEASIBILITY ANALYSIS COMMODITY INFLATION IN BUSINESS UNIT PESANTREN INDONESIA - Maulidiyah, Dewi Rahmawati; Hasib, Fatin Fadhilah (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
Hebitren is an initiative of business cooperation involving 110 pesantren throughout Indonesia which has the production of commodities. This study aims to analyze the inflationary commodities that can be produced by the pesantren business unit with a feasibility analysis approach. This study uses a case study method at Islamic boarding schools that are members of Hebitren. The data sources used are related documents, triangulation is used with other documents, and interviews with Hebitren management. Business unit pesantren in Indonesia directly or indirectly can support keeping the inflation rate throsupply-sideside inflation commodities, Some Islamic boarding schools need to be developed in provinces that are producers of inflationary commodities, such as chili, which has the most significant production in East Java province, but Islamic boarding schools in that province have not been optimized to produce chili. Some pesantren can manage their production in general commodities and have even penetrated exports, some pesantren need to increase their production to maintain the inflation rate and the government should develop pesantren located in potential areas that produce inflationary commodities still there are no Islamic boarding schools that produce these inflation commodities.